2021
DOI: 10.1111/jzs.12478
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive study of the mitogenome of the diamondback squid ( Thysanoteuthis rhombus Troschel, 1857) and the evolution of mitogenome arrangement in oceanic squids

Abstract: The diamondback squid, Thysanoteuthis rhombus, is the only currently accepted species within the family Thysanoteuthidae. In this study, the mitogenome of T. rhombus was sequenced using the Illumina NovaSeq 6000 platform. Features of the mitogenome were detected, and phylogenetic relationships among the Cephalopoda were reconstructed. Our results indicated that the mitogenome of T. rhombus had six duplicated genes and long non‐coding regions. The gene arrangement of T. rhombus was consistent with that of speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…According to previous studies (Bernt et al 2013a), four gene blocks were identi ed in Bilateria and de ned as conserved block. In Tang's study (Tang et al 2021), four complete conserved blocks were found in some cephalopods, namely ( 1) nad2-cox1-cox2-trnD-atp8-atp6; (2) nad4l-nad4 -trnH-nad5; (3) rrnS-trnV-rrnL-trnL1-trnL2-nad1; (4) nad6-cytb-trnS. In the present study, in addition to Ancistrocheirus sp, Lampadioteuthis megaleia, Stigmatoteuthis arcturi and Dosidicus gigas did not conform to the nad2-cox1-cox2-atp8, the other Oegopsida suborder species all conform to this conserved block.…”
Section: Gene Arrangementmentioning
confidence: 99%
“…According to previous studies (Bernt et al 2013a), four gene blocks were identi ed in Bilateria and de ned as conserved block. In Tang's study (Tang et al 2021), four complete conserved blocks were found in some cephalopods, namely ( 1) nad2-cox1-cox2-trnD-atp8-atp6; (2) nad4l-nad4 -trnH-nad5; (3) rrnS-trnV-rrnL-trnL1-trnL2-nad1; (4) nad6-cytb-trnS. In the present study, in addition to Ancistrocheirus sp, Lampadioteuthis megaleia, Stigmatoteuthis arcturi and Dosidicus gigas did not conform to the nad2-cox1-cox2-atp8, the other Oegopsida suborder species all conform to this conserved block.…”
Section: Gene Arrangementmentioning
confidence: 99%
“…Total genomic DNA was extracted from muscle tissue using the Easy Pure genomic DNA kit (Trans Gen Biotech Co, Beijing, China). The original sequence data (15.65 G) was deposited in NCBI's Sequence Read Archive (SRA; accession: SRR13516389), and complete mitogenome sequencing (15.62 G) was performed on an Illumina NovaSeq6000 platform (Novogene Bioinformatics Technology Co. Ltd., Tianjin, China) (Tang et al, 2021). The mitogenome was assembled using the program NOVO Plasty 3.7 (Dierckxsens et al, 2017) and then adjusted manually.…”
Section: Sample Collection and Genome Sequencingmentioning
confidence: 99%
“…Diamond squid Thysanoteuthis rhombus (Troschel, 1857), the only member of the family Thysanoteuthidae (Tang et al, 2021), grows to at least 100 cm in dorsal mantle length (DML) and 24 kg in both sexes (Roper & Jerez, 2010). The growth rate is rapid (Miyahara, Ota, Goto, & Gorie, 2006).…”
Section: Introductionmentioning
confidence: 99%